2020
DOI: 10.4025/actasciagron.v43i1.48276
|View full text |Cite
|
Sign up to set email alerts
|

Above and belowground carbon stock in a tropical forest in Brazil

Abstract: An increase in atmospheric CO2 levels and global climate changes have led to an increased focus on CO2 capture mechanisms. The in situ quantification and spatial patterns of forest carbon stocks can provide a better picture of the carbon cycle and a deeper understanding of the functions and services of forest ecosystems. This study aimed to determine the aboveground (tree trunks) and belowground (soil and fine roots, at four depths) carbon stocks in a tropical forest in Brazil and to evaluate the spatial patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
3
7
0
1
Order By: Relevance
“…The SOC on the other hand decreased with an increase in soil depth from 14.17 ± 0.35 t•C/ha to 7.00 ± 0.50 t•C/ha. Juhwan et al [109] and Dantas et al [102] indicated that the SOC decreased with an increase in soil depth which is similar to the results of this study. This is partly due to the accumulation of organic material at the soil surface, and the increased rate of organic matter decomposition in the tropics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SOC on the other hand decreased with an increase in soil depth from 14.17 ± 0.35 t•C/ha to 7.00 ± 0.50 t•C/ha. Juhwan et al [109] and Dantas et al [102] indicated that the SOC decreased with an increase in soil depth which is similar to the results of this study. This is partly due to the accumulation of organic material at the soil surface, and the increased rate of organic matter decomposition in the tropics.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, there is a negative relationship between soil density and depth as a result of the high organic matter content at the surface because organic matter is less dense than mineral grains [108]. These results are similar to those of Dantas et al [102] in a tropical forest in Brazil. Their Bulk density was however higher (0.89 g•cm −3 in the topsoil) than that found in our study.…”
Section: Discussionsupporting
confidence: 86%
“…It was varied from minimum 22.923 tC/ha (1 ha patch) to maximum 183.959 tC/ha (100 ha patch). Carbon stock values for tropical forests have also been reported in different parts of the world which are belonging to (Dantas et al, 2021;Figueiredo et al 2015) and just over (Behera et al, 2017;Hoshizaki et al, 2004) the recorded values of 10 ha, 50 ha and 100ha patch. But 1 hac patch represents very low amount carbon stock values compared to the previ- ous report, due to its smallest size through most significant disturbances among rest of the patches.…”
Section: Discussionmentioning
confidence: 89%
“…These results can be attributed to several factors related to the functioning of each forest ecosystem. First, deposits of organic residues by the native forest were an easily decomposable type of organic matter, which favours nutrient cycling and the MB‐C and microbial activity of the soil (Bini et al, 2013; Butterbach‐Bahl et al, 2013; Dantas et al, 2020; Park et al, 2012). Meanwhile, the pine plantations produced organic residues that form more lignin‐rich SOM, which is more recalcitrant to microbial degradation; and pine plantations may also have exuded compounds such as terpenes that inhibited the activity of soil microorganisms (Bini et al, 2013; Dietz et al, 2020; Olsson et al, 2019; Veloso et al, 2018; Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%